PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN NUMERASI MURID PADA MATERI SISTEM IMUNITAS FASE F SMA NEGERI 6 PADANG - Situmorang, Nike Astria; Syamsurizal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Numeracy ability is the basic ability of students to understand, use, and interact with numbers in various situations in everyday life. However, students' numeracy ability is still relatively low, this is influenced by the learning model. The purpose of this study was to determine the effect of the Problem Based Learning model on the numeracy ability of Phase F students on the immune system material.This study uses a quantitative method with a quasi-experimental design. This study uses a Posttest Only Control Group Design design with a research population of all Phase F students of SMAN 6 Padang. The research sample consisted of two classes, namely the experimental class and the control class selected using the Purposive Sampling technique. Data analysis was carried out using the Shapiro-Wilk normality test, Levene's homogeneity test, and the Independent Samples t-test hypothesis test. The results of the study showed that the average numeracy ability of the experimental class was 81.67, higher than the control class 75.76. The results of this study indicate that there is a positive influence of the Problem Based Learning model on the numeracy ability of Phase F students on the immune system material at SMAN 6 Padang.